Experimental data on 59Fe, 65Zn and 89Sr uptake by Enteromorpha linza and Cystoseira barbata from the Romanian Black Sea shore - Bologa, Alexandru S.; Chiosilă, L. (Cercetări Marine - Recherches Marines, 2026)
The following maximum concentration factors for the green alga Enteromorpha linza L. and the brown alga Cystoseira barbata (Good.et Wood.)Ag. from the Romanian Black Sea shore were experimentally determined: for 59Fe = 3,227 and 453 (August), respectively; for 65Zn = 7,147 and 2,444 (August), respectively; for 89Sr = 65 and 120 (June), respectively.